Microsurgery and endovascular treatment of posterior inferior cerebellar artery aneurysms - Sejkorová, A; Cihlář, F; Hejčl, A; Lodin, J; Vachata, P; Sameš, Martin (Neurosurgical review, 2016)
Aneurysms located on the posterior inferior cerebellar artery are rare, and treatment guidelines for them have not yet been established. In this paper, we present the results of a retrospective study which analyzes the management and treatment of 15 patients with posterior inferior cerebellar artery aneurysms from 2004 to 2013. The aneurysms were ruptured and presented with a subarachnoid hemorrhage. Of the 15 aneurysms, ten were of saccular, three fusiform, and two were dissecting. Computed tomography angiography or digital subtraction angiography revealed other aneurysms or intracerebral artery hypoplasia in seven patients. Either surgical or endovascular treatment was performed depending on the localization and morphology of the aneurysm. Six aneurysms were coiled, and surgery was performed in nine cases. Of the nine surgically treated patients, six (75%) had good outcomes. Of the six patients treated using endovascular procedures, three patients (50%) recovered. Patient outcomes were classified using the Hunt&Hess scale. Patients with Hunt&Hess 1-3 recovered without a neurological deficit. On the other hand, patients with Hunt&Hess 4-5 had a risk of up to 93% of death or a poor outcome. In two cases of endovascular and in two cases before any therapy, aneurysmal rebleeding occurred and resulted in deterioration of clinical state of the patient and a poor prognosis with high risk of death. This study shows the necessity of acute treatment of posterior inferior cerebellar artery aneurysm, of thorough diagnostic, and of interdisciplinary cooperation.
Keywords: mužské pohlaví; Retrospective Studies; Male; senioři; senioři nad 80 let; retrospektivní studie; výsledek terapie; Endovascular Procedures; Female; Humans; Prognosis; Cerebellar Diseases; lidé; Subarachnoid hemorrhage; Cerebral Angiography; Tomography, X-Ray Computed; Middle Aged; ženské pohlaví; lidé středního věku; počítačová rentgenová tomografie; nemoci mozečku; prognóza; Aneurysm; Posterior inferior cerebellar artery; Aged, 80 and over; Angiography, Digital Subtraction; Neurosurgical Procedures; Endovascular treatment; Treatment Outcome; Intracranial Aneurysm; neurochirurgické výkony; dospělí; intrakraniální aneurysma; Adult; Clipping; mikrochirurgie; digitální subtrakční angiografie; mozková angiografie; Aged; endovaskulární výkony; Microsurgery